IMPLEMENTATION OF PANCASILA VALUES IN CHARACTER EDUCATION OF THE MILLENNIAL GENERATION - Yustiani, Tia; Pandin, Moses Glorino Rumambo (Ganesha Civic Education Journal, 2024)
Education in Indonesia has not yet achieved optimal results, especially in character education for the millennial generation. Character education is very important to be instilled in children because character education is an education that develops attitudes, values, and behaviors that can give rise to noble morals with noble character, all of which are manifestations of Pancasila values. The purpose of this study is to find out how to implement Pancasila values ​​in character education. This research method uses a qualitative approach with a literature study method using research articles. The results of this method obtained ten selected articles which were then analyzed using a table with the keywords Pancasila, character education, and the millennial generation. The results of the study explain that the millennial generation must have good morals and ethics in their lives, so they will certainly never forget the noble values ​​of the Indonesian nation which will become the next generation of the nation. The implication of this study is that it can provide a better evaluation framework or instrument to measure the effectiveness of the implementation of Pancasila values ​​in the character education of the millennial generation. This is important to ensure that the efforts made have the expected impact.